An Experimental Study to Assess the Effectiveness of Aerobic Exercise on Blood Urea in Hemodialysis Patients in Selected Hospitals, Chennai - Yogalakshmi, S.; Sasikala, D.; Varughese, Santosh; Vijayalakshmi, K. (International Journal of Nursing Research, 2023)
Aim: This study was aimed to determine the effect of intradialytic aerobic exercise on blood urea in hemodialysis (HD) patients. Introduction: HD is one way to treat advanced kidney failure and can help to carry on an active life despite failing kidneys. Intradialytic exercise (IDE) is the exercise training performed during the HD session to increase the patient’s strength and endurance. Materials and Methods: A quasi-experimental study was carried out among 60 adult patients on HD (30 each in control and experimental groups), selected by consecutive sampling technique, at selected tertiary care centers in Chennai. The baseline characteristics and pretest blood urea were collected from both the groups and the intradialytic aerobic exercise was administered for 8 weeks (3 times/week) among the experimental group of patients. Then Post-test I and II blood urea were assessed in both the groups at end of 4th and 8th week. The data were analyzed in SPSS 22. Results: IDE showed a significant effect in reducing blood urea (mg/dl) among experimental group of participants than control group in post-test I (76.73 ± 17.58, 93.20 ±19.24) and in post-test II (62.23 ± 13.28, 90.20 ±19.60) at P = 0.001. There was no significance difference in baseline data/pre-test between experimental and control group pre-test (103.53 ± 30.03, 103.70 ± 30.46). Conclusion: This study reveals that intra dialytic aerobic exercises is beneficial in terms of reducing blood urea, as a supplementary therapy for HD patients.